Qualitative Assessment of a Customized Anti-hepatic Herbal Formulation in Bangladesh - Rahman, Md Hafizur; Rokeya, Begum; Mosihuzzaman, Mohammed; Haque Khan, Md Shahinul (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Qualitative assessment of herbal formulations is used in pre-health care of many diseases. The potency, composition and safety of herbal formulation are serious concerns in Bangladesh. Therefore, the aim of the present study was to evaluate the qualitative assessment of a customized anti-hepatic herbal formulation in Bangladesh. Isolation of compounds, toxic metals analysis, phytochemical screening, microbial test and determination of SGPT and SGOT level of hepatic model rats were focused in this study. The phytochemical screening revealed the presence of phenol, saponins and tannins. In chemical study, four known compounds were isolated from the formulation (Sodium benzoate, methyl-4-hydroxybenzoate, 4-hyroxybenzaldehyde and 4-hydroxy- 3-methoxybenzaldehyde). The results of microbial purity and toxic metals analysis were in favorable limit although the levels of SGOT and SGPT were raised non-significantly. So, based on the study it has been concluded that quality assessment is urgently required for this type of customized herbal formulations. Dhaka Univ. J. Pharm. Sci. 21(1): 59-67, 2022 (June)